Oral Candida albicans isolates from HIV-positive individuals have similar in vitro biofilm-forming ability and pathogenicity as invasive Candida isolates - Junqueira, Juliana Campos [UNESP]; Fuchs, Beth B.; Muhammed, Maged; Coleman, Jeffrey J.; Suleiman, Jamal M. A. H.; Vilela, Simone F. G. [UNESP]; Costa, Anna C. B. P. [UNESP]; Rasteiro, Vanessa M. C. [UNESP]; Jorge, Antonio O. C. [UNESP]; Mylonakis, Eleftherios (Biomed Central Ltd., 2011)
Background: Candida can cause mucocutaneous and/or systemic infections in hospitalized and immunosuppressed patients. Most individuals are colonized by Candida spp. as part of the oral flora and the intestinal tract. We compared oral and systemic isolates for the capacity to form biofilm in an in vitro biofilm model and pathogenicity in the Galleria mellonella infection model. The oral Candida strains were isolated from the HIV patients and included species of C. albicans, C. glabrata, C. tropicalis, C. parapsilosis, C. krusei, C. norvegensis, and C. dubliniensis. The systemic strains were isolated from patients with invasive candidiasis and included species of C. albicans, C. glabrata, C. tropicalis, C. parapsilosis, C. lusitaniae, and C. kefyr. For each of the acquired strains, biofilm formation was evaluated on standardized samples of silicone pads and acrylic resin. We assessed the pathogenicity of the strains by infecting G. mellonella animals with Candida strains and observing survival.Results: The biofilm formation and pathogenicity in Galleria was similar between oral and systemic isolates. The quantity of biofilm formed and the virulence in G. mellonella were different for each of the species studied. on silicone pads, C. albicans and C. dubliniensis produced more biofilm (1.12 to 6.61 mg) than the other species (0.25 to 3.66 mg). However, all Candida species produced a similar biofilm on acrylic resin, material used in dental prostheses. C. albicans, C. dubliniensis, C. tropicalis, and C. parapsilosis were the most virulent species in G. mellonella with 100% of mortality, followed by C. lusitaniae (87%), C. novergensis (37%), C. krusei (25%), C. glabrata (20%), and C. kefyr (12%).Conclusions: We found that on silicone pads as well as in the Galleria model, biofilm formation and virulence depends on the Candida species. Importantly, for C. albicans the pathogenicity of oral Candida isolates was similar to systemic Candida isolates, suggesting that Candida isolates have similar biofilm-forming ability and virulence regardless of the infection site from which it was isolated.